Onicopatias en ancianos. Reporte de 71 casos - Patricia Chang; Kathia Domínguez (Our Dermatology Online, 2016)
Introduction: The nails present various changes and diseases due to age, and the elderly are no exception to this. Aims: To learn about the most frequent nail diseases in elderly patients of our hospital unit. Methodology: A descriptive study was performed on patients hospitalized at Hospital General de Enfermedades IGSS in medical services during February and March 2015, to investigate the occurrence of nail diseases in hands and feet of elderly patients. All the patients had a complete exam of finger and toe nails. Results: The alterations detected in fingernails were: onychorrhexis, 36 (22.99%); half-and-half nails, 5 (5.75%); Leukonychia apparent, 3 (3.45%), onychoschizia, 3 (3.45%); proximal fold hematoma due to oximeter, 3 (3.45%); onycholysis, 3 (3.45%); splinter hemorrhages, 3 (3.45%); pterygium, 2 (2.30); worn-down nails, 2 (2.30); onychodystrophy, 1 (1.15%); nail biting, 1 (1.15%); parrot beak nails, 1 (1.15%), Beau's lines, 1 (1.15%); paronychia, 1 (1.15%); trauma, 1 (1.15%); Beau's ridges, 1 (1.15%). At feet level the alterations found were: onychomycosis, 31 (29.52%); onychogryphosis, 16 (15.24%); pterygium, 8 (7.62%); overriding toes, 5 (4.76%); platonychia, 5 (4.76%); pincer nails, 4 (3.81%); frictional melanonychia, 4 (3.81%); onychorrhexis, 4 (3.81%); onychodystrophy, 4 (3.81%); hematoma, 3 (2.86%), onycholysis, 2 (1.90%), koilonychias, 2 (1.90%), Beau's ridges, 2 (1.90%); Onychomadesis, 1 (0.95%); tile-shaped nails, 1 (0.95%); longitudinal groove, 1 (0.95%); distal nail embedding, 1 (0.95%); anonychia, 1 (0.95%); micronychia, 1 (0.95%); pachionychia, 1 (0.95%); dyschromia, 1 (0.95%). Conclusion: The alterations of finger and toe nails in the elderly are not exclusive of this group as they occur in the general population except that in the elderly, the most frequent are onychorrhexis in hands and onychogryphosis in feet.